Bank Accounts, Nonbank Financial Transaction Products, and Food Insecurity among Households with Children. Issue 3 (7th September 2017) - Fitzpatrick, Katie
Abstract : Low‐ and moderate‐income households with children often face considerable difficulties in ensuring enough financial resources for adequate consumption. With households in both the December 2008 current population survey (CPS) food security supplement and the January 2009 CPS unbanked and underbanked supplement, I investigate the relationship between bank account ownership, nonbank financial transaction products, and food security of households with children. Unbanked households and households that use alternative financial service transaction products are more likely to experience very low food security and food insecurity than other households. Currently unbanked but previously banked households as well as underbanked households face the greatest risk of food insecurity. Policies to improve the consumption adequacy of households with children may benefit from a multifaceted approach that addresses their banking and financial transaction needs.